PENGEMBANGAN STRATEGI PEMBELAJARAN YANG EFEKTIF DI TENGAH PANDEMI COVID 19 - Yulia, Tantri (Sekolah Tinggi Teologi Kristus Alfa Omega, 2020)
Covid 19 pandemic has caused changes in various fields, including education. There are some problems that arise in the selection of learning strategies during the Covid 19 pandemic. The research method used in this research is development research, namely research used to test product quality using quantitative methods as the primary method and examining users with qualitative methods as secondary methods. The result of the research is the level of the development of effective learning strategies during the COVID-19 pandemic at STT Kristus Alfa Omega Semarang in the moderate category or less of the maximum value is not proven